Thermal Characteristics of the Permafrost within an Active Rock Glacier (Murtèl/Corvatsch, Grisons, Swiss Alps) - Mühll, Daniel Vonder; Haeberli, Wilfried (Journal of Glaciology, 1990)
Abstract Temperatures from a bore hole through an active rock glacier in the eastern Swiss Alps are presented and thermal conditions within the slowly creeping permafrost are analyzed. Present mean annual temperature in the uppermost part of the permafrost is −3°C. Permafrost is 52 m thick and reaches heavily fissured bedrock. Thermal conductivity as determined in situ from seasonal temperature variations and measured in a cold laboratory using frozen samples is close to 2.5–3.0 W m −1 °C −1 . Vertical heat flow is anomalously high (around 150 mW m -2 ), probably due to heat advection from circulating ground water or air within the fissured bedrock zone. Beneath this zone, which could in fact represent a non-frozen intra-permafrost layer or “talik”, relic permafrost from past centuries may possibly exist as indicated by a corresponding heat-flow inversion. Given the current temperature condition at the surface of the rock glacier and the fact that the twentieth century is among the warmest in post-glacial time, permafrost conditions may be assumed to have existed during the whole of the Holocene and, hence, during the entire time of rock-glacier formation.